Charcoal-yeast extract agar: primary isolation medium for Legionella pneumophila. - Feeley, J C (1979)
Charcoal-yeast extract agar is a new bacteriological medium that supports excellent growth of the Legionella pneumophila. It results from modifications made in an existing L. pneumophila medium, F-G agar. Yeast extract, instead of an acid hydrolysate of casein, serves as the protein source. Beef extractives and starch are not added. Activated charcoal (Norit A or Norit SG) is included at 0.20% (wt/vol). Comparison of charcoal-yeast extract and F-G agars showed that a greater number of colony-forming units of L. pneumophila was recovered from a standardized tissue inoculum on charcoal-yeast extract agar (4.35 x 10(6) colony-forming units) than on F-G agar (4.85 x 10(4) colony-forming units). Macroscopic colonies of L. pneumophila were visible on the new medium within 3 days, whereas 4 days of growth was required on F-G agar.